La transición de los estudiantes de EMS a la Universidad. Aportes para la reflexión curricular - Celia Carrera Hernández; Oscar Luis Ochoa Martínez (iQuatro Editores, 2021)
Este estudio analiza el proceso de transición de la Educación Media Superior a la Universidad desde el rendimiento académico obtenido a partir de las puntuaciones obtenidas en el examen de ingreso y los promedios alcanzados en el primer y segundo semestre de Licenciatura. El enfoque es cuantitativo con un alcance correlacional, el diseño no experimental de tipo transeccional o transversal. (Hernández, Fernández y Baptista, 2006). Los instrumentos utilizados fueron el examen de ingreso EXAD I y las actas de evaluación de los primeros semestres de la licenciatura. El examen de ingreso se aplicó a 1051 estudiantes de los 11 campus de la UPNECH, pero para el estudio solo se consideraron 184 estudiantes que corresponden a la Unidad Chihuahua. Los resultados ponen de manifiesto que existe una correlación significativa entre las puntuaciones obtenidas en el examen de ingreso y las calificaciones de los primeros dos semestres cursados. Abstract This study analyzes the process of transition from high school to university considering academic performance drawn from scores obtained from diagnostic examinations for diagnostic purposes and results obtained from assessment records during a student's the first and second semester of the degree program taken. The approach is quantitative with a correlational scope; the design is nonexperimental cross-sectional (Hernández, Fernández & Baptista, 2006). The instruments used were the diagnostic examination EXADI 1 (National Diagnostic Examination), and the students' assessment records which corresponded to their first and second semester of the degree program taken. The diagnostic examination was applied to 1, 051 students from 11 National Pedagogical Universities of the State of Chihuahua, however, for this study, we only considered 184 students which were attending classes at the Chihuahua Unit. The results manifest the existence of a significant correlation between scores obtained on the diagnostic examination and assessment records of the first two semesters of the degree program taken.